Effect of different attributes of the mimic human lumbar spine biomechanics material structure change by finite element analysis - Da-Ping Qin (Springer, 2021)
Abstract In this study, we compared stress changes and quantity effect relationships from 3D finite element models of normal and degenerative lumbar segments. We further defined the mechanisms causing alterations in mechanical stability the control of normal and degenerative lumbar segments using traditional Chinese medicine. The characteristics of the stress change and the quantity effect relationships of the three-dimensional finite element model of normal and degenerative lumbar segments were compared. The mechanism(s) leading to changes in mechanical stability and the intervention and balance between normal and degenerative lumbar segments of the traditional Chinese medicine was analyzed. The change trend of stress and strain was compared with the three dimensional finite element model under different motion states of normal lumbar vertebrae. A 3D-FEM of degenerative lumbar segments L4 ~ 5 of the human spine was established to simulate the physiological and pathological changes of the lumbar spine in response to flexion, extension, lateral bending and torsion. The stress changes in the normal and degenerative lumbar vertebrae were assessed through external force interventions and the response to TCM. Stress in the degenerative lumbar vertebrae changed according the external load. Stress and strain were compared in the FEM model under a range of motion states. Components of the human lumbar vertebrae including the cortical vertebrae, cancellous bone, endplates, fibrous rings, and facet articular processes were investigated. The elastic modulus of the nerve roots and the posterior marginal structures of the vertebral body increased with lumbar degeneration. Under stress trends in normal lumbar and different degrees of degenerative lumbar structures including cortical bone, loose bone, terminal plate, fiber ring, nucleus, small articular processes, nerve roots and posterior structures. In normal lumbar spine, 20%, 50%, 70% lumbar degeneration, 106 different lumbar anterior flexion 30 and posterior extension with different external forces showed that ANOVA F was between 3.623 and 11.381 and P changed between 0.001 and 0.05.It is clear that in the lumbar movement segments under different pressure intervention, the changes in the degree of degeneration are significantly different from each constituent structure, among which the trend of expected change between the constituent structures of the lumbar anterior flexion 30 is particularly obvious. The stress distribution in the intervertebral discs were influenced by TCM, and the space in the spinal canal enlarged so that nerve root stress decreased, vertebral body stress increased, and facet processes and pedicle stress in the posterior regions exceeded those of the anterior flexion position. The internal stress of the intervertebral disc increased in the flexion compared to the extension position, gradually increasing from top to bottom. The stress concentration point of the degenerative lumbar disc is significantly greater than the stress in the normal lumbar disc stress distribution area, and increases with the degree of degeneration. Compared with the load capacity of normal lumbar and mild (15% reduction), moderate (40% reduction) lumbar disc protrusion model in bending, extension, axial rotation, lateral bending, the results found that the load transmission of lumbar disc degeneration model to different degrees has also changed, so its compression stiffness, strain distribution and size are also different. TCM can improve and treat lumbar disc disease through its ability to regulate the mechanical environment of degenerative lumbar vertebrae. Compared to the FEM models of the lumbar vertebrae, lumbar degenerative changes could be assessed in response to alterations in the biomechanical environment. These findings provide a scientific basis for the popularization and application of TCM to prevent and treat spinal degenerative disease.